Sexual Arousal and Sexual Fantasy: The Influence of Gender, and the Measurement of Antecedents and Emotional Consequences in Macau and the United States. Issue 1 (2nd January 2016) - Wu, Yan; Ku, Lisbeth; Zaroff, Charles M.
ABSTRACT: Objectives: Cross-cultural research was conducted to elucidate the relative influences of culture and gender on human sexuality. Methods: 353 male and female undergraduate students from universities in the United States and Macau completed self-report measures assessing sexual fantasy and arousal . Results: Males reported significantly more frequent sexual fantasy/arousal than females. Additionally, significant differences in the age of initial sexual arousal were found. Males from the United States reported the earliest age of initial arousal, followed by males from Macau, females from the United States, and females from Macau. Males from each region reported a significantly younger age of initial sexual fantasy than females within the same region. The Macau group reported significantly less frequent sexual arousal than the U.S. group. Conclusions: Sexual fantasy and arousal are susceptible to cultural and gender-based influences, whose strength varies by outcome measures.